MEASUREMENTS OF THE OXYGEN ISOTOPIC RATIO OF ATMOSPHERIC CO_2 AT SYOWA STATION, ANTARCTICA - ムラヤマ, ショウヘイ; ナカザワ, タカキヨ; アオキ, シュンジ; モリモト, シンジ; シミズ, アキラ; ハヤシ, マサヒコ; カワグチ, サダオ; タナカ, マサユキ; MURAYAMA, Shohei; NAKAZAWA, Takakiyo; AOKI, Shuhji; MORIMOTO, Shinji; et al. (National Institute of Polar Research, 1996)
P(論文) Ground-based and aircraft measurements of the δ^<18>O of atmospheric CO_2 were made at Syowa Station, Antarctica during 1989 and 1990. To minimize the possibility of exchange of oxygen atoms between CO_2 and water during storage in sampling flasks, CO_2 was extracted from each air sample at the station within a few days of its collection. The maximum of the seasonal δ^<18>O cycle at the station appeared in summer and the minimum in winter. The peak-to-peak amplitude of the cycle was 0.27‰. δ^<18>O of CO_2 was slightly lower in the upper troposphere than in the middle and lower troposphere over the station during the measurement period. These results are in good agreement with those at Cape Grim, Tasmania and over Bass Strait. From a comparison of the CO_2 measurements at and over Syowa Station and δ^<18>O at other stations, it is suggested that seasonally dependent atmospheric transport to the Antarctic region is one of the important processes determining the seasonal cycle and the height variation of δ^<18>O of CO_2 at the station. departmental bulletin paper